Pelatihan Strategi Komunikasi dalam Pengamalan Nilai-Nilai Kebangsaan melalui Komunikasi Keluarga - Dini Nur Fadhillah; Suhaeri; Fadli Tri Hartono; Diny Fitriawati; Cevi Mochamad Taufik; Didin Sabarudin; Ira Lusiawati; Gita Eka Sila; Rizqi Ghassani; Krisna Aditya (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
The ever-evolving digital media has had an impact on the dynamics of national awareness among the younger generation today, such as a weakening understanding and practice of Pancasila and low community resilience to the influence of globalisation. Therefore, a strategy is needed to practise national values. This community service activity aims to conduct family communication training as a strategy to practise national values. This activity employs a Community-Based Participatory Research (CBPR) approach. The results of this community service activity indicate that family communication in promoting national values can be developed through a combination of conformity orientation and conversation orientation. Thus, the family communication skills developed can be balanced with actions that foster mutual benefit among families and the community.